2020
DOI: 10.1080/15376494.2020.1717693
|View full text |Cite
|
Sign up to set email alerts
|

A review on non-classical continuum mechanics with applications in marine engineering

Abstract: Marine structures are advanced material and structural assemblies that span over different length scales. The classical structural design approach is to separate these length scales. The used structural models are based on classical continuum mechanics. There are multiple situations where the classical theory breaks down. Non-classical effects tend arise when the size of the smallest repeating unit of a periodic structure is of the same order as the full structure itself. The aim of the present paper is to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These novel materials find important applications in the most diverse fields of engineering, nanotechnology, biotechnology, and even medicine. Specific examples of the different applications of complex architectured materials include, but are not limited to, biological implants [1,2], lightweight aerospace, automobile and naval structures [3,4], metamaterials designed for wave-guiding and vibration control [5][6][7], and even micro/nano-electromechanical devices [8,9]. In all these applications, the ability to achieve accurate predictions is paramount to deliver optimal designs and performance once these complex systems are deployed in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These novel materials find important applications in the most diverse fields of engineering, nanotechnology, biotechnology, and even medicine. Specific examples of the different applications of complex architectured materials include, but are not limited to, biological implants [1,2], lightweight aerospace, automobile and naval structures [3,4], metamaterials designed for wave-guiding and vibration control [5][6][7], and even micro/nano-electromechanical devices [8,9]. In all these applications, the ability to achieve accurate predictions is paramount to deliver optimal designs and performance once these complex systems are deployed in the field.…”
Section: Introductionmentioning
confidence: 99%
“…The most well-known and studied included long-range interatomic and intermolecular interactions as well as material heterogeneity at micro-and nano-scales [10][11][12]. However, nonlocal interactions can also be generated at the macroscale by means of intentionally nonlocal designs [6] and medium heterogeneity [4,[13][14][15]. Since the source of the nonlocal effects are typically specific to a material scale, the corresponding effects were often assumed to be localized at the respective scale while becoming negligible once integrated over the larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical investigations have shown that, irrespective of the spatial scale, size-dependent or nonlocal effects can become prominent in the response of several structures in the most diverse fields of engineering, nanotechnology, biotechnology, and even medicine [1][2][3][4][5][6][7][8]. The study and analysis of nonlocal effects has increasingly become an important component of structural design and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The study and analysis of nonlocal effects has increasingly become an important component of structural design and analysis. Specific examples of size-dependent structures include sensors, biological implants, micro/nano-electromechanical devices and even macroscale structures such as stiffened panels in naval and aerospace applications [4][5][6][7][8]. In the case of microand nano-structures, for example those involving carbon nanotubes or graphene sheets, nonlocal effects can be traced back to interatomic interactions, and even medium heterogeneity [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation